Density Functional Theory Study of Reaction Equilibria in Signal Amplification by Reversible Exchange. Issue 19 (7th October 2021) - Lin, Kailai; TomHon, Patrick; Lehmkuhl, Sören; Laasner, Raul; Theis, Thomas; Blum, Volker
Abstract: The front cover artwork is provided by the groups of Prof. Thomas Theis (North Carolina State University) Prof. Volker Blum (Duke University). The image shows the reaction network of Signal Amplification by Reversible Exchange (SABRE), elucidated by density functional theory (DFT). Read the full text of the Review at 10.1002/cphc.202100204 . Abstract : "We provide an in‐depth theoretical analysis of key chemical equilibria in Signal Amplification by Reversible Exchange (SABRE) through density functional theory calculations to characterize the likely reaction network…" This and more about the story behind the front cover can be found in the Article at 10.1002/cphc.202100204 .